Esophageal perforation in an 80-year-old patient following transesophageal echocardiography: A case report - Gabriella Nucera; Giovanna Petazzi; Francesco Cavaleri; Marina Molgora; Andrea Beretta (Advances in Medicine, Psychology, and Public Health)
We report a rare case of esophageal perforation in an 80-year-old female patient following transesophageal echocardiography (TEE). This procedure was imperative for evaluating the presence of thrombi in the right atrial appendage before an endoscopic closure of the appendage, particularly due to her history of atrial fibrillation and recent cerebral hemorrhage while on anticoagulant therapy. This case highlights the inherent risks associated with TEE, especially in the elderly with complicating factors such as osteophytic changes and a history of anticoagulation, but also underscores the importance of thorough pre-procedural assessment and careful monitoring. Our findings align with the literature, emphasizing the elevated risk of esophageal injury in elderly patients during TEE and the need for heightened vigilance in this population.